- #1

desic

- 4

- 0

**r**=cos(theta)

**x**+sin(theta)

**y**

**theta**=-sin(theta)

**x**+cos(theta)

**y**

show this is non-coordinate basis, i.e. show commutator non-zero.

I try to apply his formula 2.7, assuming

V1=cos(theta), V2=sin(theta)

W1=-sin(theta), W2=cos(theta)

x(r)=r cos(theta)

y(r)=r sin(theta)

x(theta)=cos(theta)

y(theta)=sin(theta)

These parametrics I got from integrating back from the components of

**r**and

**theta**

I believe the component of

**x**should be (sin(theta))/r, however I get (sin(theta) - r sin(theta))/r.

would appreciate any help